Apakah Pengungkapan Environmental, Social, Dan Governance Meningkatkan Profitabilitas? Bukti Empiris Dari Industri Manufaktur - Suroto Suroto; Tri Nurdyastuti; Elfarrastya Yun Mustikojavatri (Excellent, 2026)
This study aims to analyze and provide empirical evidence of the influence of Environmental, Social, and Governance disclosure on the profitability of manufacturing companies. This study uses a quantitative approach with data drawn from annual reports and sustainability reports of companies listed on the stock exchange during the 2019 2023 period. The analytical methods used include the classical assumption test, t-test, and linear regression to measure the relationship between Environmental, Social, and Governance disclosure variables and manufacturing company profitability, as measured by indicators such as Return on Assets (ROA). The results show that Environmental disclosure has a positive but insignificant effect on profitability, Social disclosure has a positive but insignificant effect on profitability, while Governance disclosure has a positive but insignificant effect on profitability. The R2 value is 0.232, or 23.2%, indicating that Environmental, Social, and Governance disclosures have a 23.2% effect on profitability in manufacturing companies, with the remaining 76.8% being influenced by other variables not included in this study.